Letters of John M. Fitzsimmons (as filmed by the AJCP) [M437b] - Fitzsimmons, John M., -1860.; Australian Joint Copying Project; National Library of Australia; State Library of New South Wales (Canberra : Australian Joint Copying Project, 1950)
Five letters 1841-47 from John Fitzsimmons (d. 1860), surgeon, to his brother, written from Hartley, New South Wales, mainly discussing family matters but also commenting on unemployment in the colony. One letter, 1871, from his daughter concerning the death of her father and family matters. Six receipts and small notes including one about James Slatterly and another about the burial of Elizabeth Faulks.
Filmed as part of the Australian Joint Copying Project by the National Library of Australia and the State Library of New South Wales.
National Library of Australia holds microfilm master.
With: J. P. Ricou. Journal, 1872.
Australian Joint Copying Project handbook. Part 8 : Miscellaneous [M series]
Australian Joint Copying Project miscellaneous series M437.
Also available online
Keywords: Fitzsimmons, John M., -- -1860 -- Diaries; Slattery, James; Faulks, Elizabeth -- Death and burial; Unemployment -- New South Wales